Analisis Potensi Think Pair Share dalam Pemberdayaan Keterampilan Metakognitif Siswa Laki-Laki dan Perempuan - Sele, Yunawati (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
Think Pair Share (TPS) as one of cooperative learning has been reported to be potentially used in the empowerment of students’ metacognitive skills. But the report has not been linked to gender differences. The purpose of this study was to analyze the potential use of TPS in the empowerment of metacognitive skills of male and female students. This study was conducted in the first semester of 2015/2016 academic year. The research subjects were the students of class X of State Senior High School 6 Malang. The instruments used were an essay test and a rubric of metacognitive skills. The data obtained were then tested for the normality and homogeneity of the data, and further analyzed using Ancova test. The analysis showed a significance value of p = 0.785 or > 0.05 which means the TPS learning has equal potential in empowering metacognitive skills of male and female students. The implementation of TPS learning can provide equal opportunities for male and female students to be involved in learning and provide the same demands to explore learning material.